Hidden costs of flexible work: Employers’ perception - Dias, Carolina Cravo (2021)
In a context where labor flexibility is increasingly a choice for companies to reduce organizational costs and increase their competitiveness in the labor market, it is pertinent to study the nature of the motivations behind the use of FWA, as well as the advantages and disadvantages associated with these types of contract. This research, of a qualitative and exploratory nature, explores these dimensions by placing the employer at the center of the analysis, a poorly researched perspective. HR managers of companies in Portugal were interviewed (n=8). The empirical information, gathered from semi-directive interviews, suggested that the stable employment contract remains the most recurrent option, at about 77.5%. Flexible hiring, on the other hand, responds to the very particular needs of the company, namely changes in demand. Besides, the conversion of flexible contracts into stable ones appears, in some cases, as a reward for the good performance of the employees. Companies recognize the advantages of flexible contracts as well as some negative consequences. Although the recognition of hidden costs has not been explicit, there are indications of concerns such as workers' motivation. The results obtained may be useful for companies to consider their options as to the type of employment relationship they intend to implement, as well as to elucidate policymakers as to the factors that may influence companies' decisions. However, they should be analyzed with caution. The sample is small and includes only companies that have shown themselves to be available. Nevertheless, it opens space for future more extensive research.